Swear words in American communicative culture and the problem of their translation into Russian - M M Kozyreva (Russian journal of linguistics: Vestnik RUDN, 2012)
The article deals with some peculiarities of English swear words used by well-educated representatives of American communicative culture, and the problem of their translation into Russian. The data was taken from the film Just Go with It.